2015
DOI: 10.1016/s0140-6736(14)61945-0
|View full text |Cite
|
Sign up to set email alerts
|

Fall rates in hospital rehabilitation units after individualised patient and staff education programmes: a pragmatic, stepped-wedge, cluster-randomised controlled trial

Abstract: State Health Research Advisory Council, Department of Health, Government of Western Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
250
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(258 citation statements)
references
References 34 publications
3
250
0
5
Order By: Relevance
“…Eleven trials were cluster-randomised trials (Beck 2016; Becker 2003; Dyer 2004; Jensen 2002; Kerse 2004; McMurdo 2000; Neyens 2009; Ray 1997; Salvà 2016; Walker 2015; Whitney 2017; 3470 participants), and two were individually randomised (Rubenstein 1990; Shaw 2003; 756 participants). Whitney 2017 was also a cross-over trial.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven trials were cluster-randomised trials (Beck 2016; Becker 2003; Dyer 2004; Jensen 2002; Kerse 2004; McMurdo 2000; Neyens 2009; Ray 1997; Salvà 2016; Walker 2015; Whitney 2017; 3470 participants), and two were individually randomised (Rubenstein 1990; Shaw 2003; 756 participants). Whitney 2017 was also a cross-over trial.…”
Section: Resultsmentioning
confidence: 99%
“…However, although falls rates were significantly reduced among patients who directly received the education, falls rates were also reduced in the subgroup of patients with poorer levels of cognition, who did not receive the education 14. These results suggested that delivering the education as a ward level intervention also caused a ward level change which was effective in reducing falls.…”
Section: Introductionmentioning
confidence: 92%
“…This patient education programme, called the Safe Recovery programme, significantly reduced falls and injurious falls (adjusted rate ratio 0.65, 95% CI 0.42 to 0.88) in hospital rehabilitation wards 1415 The Safe Recovery programme has been described extensively and piloted previously 14–17. It consists of providing eligible, older patients with multimedia information (DVD and workbook) about falls and falls prevention and tailored follow-up by a trained health professional, who aims to personalise the information for each patient.…”
Section: Introductionmentioning
confidence: 99%
“…35 One study 36 found a one-on-one patient education program, targeted at those without cognitive impairment, to be effective in preventing falls in a rehabilitation settings and some carryover of this impact to fall prevention in people with cognitive impairment, presumably due to changes in staff behaviour and awareness. 37 …”
Section: Hospital and Residential Carementioning
confidence: 99%